Text Linguistics of â€œTextualityâ€: Making a Sequence of Sentences Communicative English Written Texts - Yalmiadi Yalmiadi; Yohannes Telaumbanua (Jurnal Ilmiah Pendidikan Scholastic, 2023)
Textuality makes a sequence of sentences a communicative English written text. It, nonetheless, hardly becomes a major theme of foreign language learning in the Indonesian English Writing Classes/context nowadays. This study, therefore, aimed at diagnosing the “incorrect/missing uses of the seven elements of the textuality in the students’ cause and effect essay. Qualitatively, Politeknik Negeri Padang was the locus of the study. The 2nd-year ED students (n=32) were the research participants selected through the convenience sampling techniques. The documentation and observation were the techniques of data collection while the 1967 Corder’s Clinical elicitation was exercised as ways of analysing the data. The findings disclosed that the students missed using nominal substitution and lexical cohesion of repetition and synonym along with incorrectly used verbal and clausal substitution, nominal, verbal and clausal ellipsis, anaphoric and cataphoric references, and lexical cohesion of grammatical and lexical collocations. They, however, succeeded in correctly using three different types of conjunctions and coherence though they flopped to utilise the acceptable phrases of drawing a conclusion. Hyponymy, metonymy and antonymy were ignored. In conclusion, the deficiencies made the students’ sequences of sentences flawed and characterless. It, therefore, encourages EFL teacher to place emphasis on teaching textuality in the English Writing Classes.